(untitled) (Journal of Applied Oral Science, 2003)
Background. Oral mucositis is a common complication of some malignancies treatment, causing therapeutic modifications due to patient's debilitation, which often interferes with the prognosis of the disease. Many attempts have been made to find an optimal treatment or preventive method to minimize the severity of oral mucositis. Several studies have shown good results with the use of low-energy laser, with the aim of accelerating the process of wound healing and promoting pain relief. Methods. Patients (n=18) who developed oral mucositis during chemotherapy and/or radiotherapy were submitted to low-energy laser applications until cessation of symptoms. Mucositis severity was scored by an oral mucositis scale based on clinical features and by an oral toxicity scale from the National Cancer Institute based on the ability to swallow; pain severity was scored by subjects on a visual analogue scale before and after the applications. Results. Immediate pain relief was achieved in 66.6% of the patients after the first application. Based on the functional scale, mucositis grade III (not capable to eat solids) was reduced in 42.85% of the cases. According to the scale based on the clinical features, mucositis grade IV (ulcerative lesions) was reduced in 75% of the patients that presented this grade of mucositis at the beginning of laser therapy. Conclusions. Low-energy laser was well-tolerated and showed beneficial effects on the management of oral mucositis, improving the quality of life during the oncologic treatment.